Morphine Addiction and Oxidative Stress: The Potential Effects of Thioredoxin-1 - Zeng, Xian-Si; Geng, Wen-Shuo; Wang, Zhan-Qi; Jia, Jin-Jing (Frontiers in Pharmacology, 2020)
Long-term administration with morphine for the management of chronic pain will result in tolerance to its analgesic effect, even drug dependence. Numerous studies have demonstrated significant redox alteration in morphine dependence and addiction. Thioredoxin-1 (Trx-1) play important roles in controlling the cellular redox balance. In recent years, several recent studies have demonstrated that Trx-1 may be a promising novel therapeutic target for morphine addiction. In this article, we firstly review the redox alteration in morphine addiction. We also summarize the expression and the protective roles of Trx-1 in morphine dependence. We further highlight the protection of geranylgeranylacetone (GGA), a noncytotoxic pharmacological inducer of Trx-1, in morphine-induced conditioned place preference. In conclusion, Trx-1 may be very promising for clinical therapy of morphine addiction in the future.